O gênero Beloesthes Thomson e nota sinonímica em Alcathousites Gilmour (Coleoptera, Cerambycidae, Lamiinae, Acanthocinini) The genus Beloesthes Thomson and synonymical note on Alcathousites Gilmour (Coleoptera, Cerambycidae, Lamiinae, Acanthocinini) - Miguel A. Monné (Revista Brasileira de Entomologia, 2004)
O gênero Beloesthes Thomson, 1864 e B. megabasoides Thomson, 1864 são redescritos e figurados. Alcathousites asperipennis (Fairmaire & Germain, 1859) comb. nov. (antes em Leiopus) = Alcathousites chaclacayoi Gilmour, 1962 syn. nov. The genus Beloesthes Thomson, 1864 and B. megabasoides Thomson, 1864 are redescribed and figured. Alcathousites asperipennis (Fairmaire & Germain, 1859) comb. nov (from Leiopus) = Alcathousites chaclacayoi Gilmour, 1962 syn. nov.